Haptics control of an arm exoskeleton for virtual reality using PSO-based fixed structure H∞ control. (14th May 2019) - Silawatchananai, Chaiyaporn; Parnichkun, Manukid
This article proposes a robust haptics control algorithm for an arm exoskeleton in virtual reality application that guarantees the robustness of the force displaying performance. The developed arm exoskeleton allows the user to sense the profile of virtual objects through joints at wrist, elbow, and shoulder. Forces exerted by the user are directly measured by load cells attached to the links, which are used to determine the corresponding velocity command based on virtual impedance. Due to the imperfection of modeling and the measurement noises from load cells and encoder quantization, the force displaying performance of the device tends to degrade with increasing oscillation, causing permanent damages to the device and user. To solve this problem, a Particle swarm optimization (PSO)-based fixed structure H∞ controller is proposed to control the developed arm exoskeleton. The control performance of the proposed controller is evaluated by both simulation and experiment. The results show that the proposed controller can achieve better tracking performance in comparison with proportional–integral–derivative controller in terms of less oscillation and fast response.